Emerging Strategies for the Bioremediation of the Phenylurea Herbicide Diuron - Li, Jiayi; Zhang, Wenping; Lin, Ziqiu; Huang, Yaohua; Bhatt, Pankaj; Chen, Shaohua (Frontiers in Microbiology, 2021)
Diuron (DUR) is a phenylurea herbicide (PUH), widely used for the effective control of most annual and perennial weeds in farming areas. The extensive use of diuron has led to its widespread presence in soil, sediment, and aquatic environments, which poses a threat to non-target crops, animals, humans, and ecosystems. Therefore, the removal of DURdiuron from contaminated environments has been a hot topic for researchers in recentthe last decades. Bioremediation seldom leaves harmful intermediate metabolites and is emerging as the most effective and eco-friendly strategy for removing diuron from the environment. Microorganisms, such as bacteria, fungi, and actinomycetes, can use DURdiuron as theira sole source of carbon. Some of them have been isolated, including organisms from the bacterial genera Arthrobacter, Bacillus, Vagococcus, Burkholderia, Micrococcus, Stenotrophomonas, and Pseudomonas, and fungal genera Aspergillus, Pycnoporus, Pluteus, Trametes, Neurospora, Cunninghamella, and Mortierella. A number of studies have investigated the toxicity and fate of DURdiuron, its degradation pathways and metabolites, and diuron-degrading hydrolases and related genes. However, few reviews have focused on the the microbial degradation and biochemical mechanisms of DURdiuron. The common microbial degradation pathway for DURdiuron is via transformation to 3,4-dichloroaniline (3,4-DCA), which is then metabolized through two different metabolic pathways:, dehalogenation and hydroxylation. , 3,4-DCA cancould bethe products of which are further degraded viathrough cooperative metabolism. Microbial degradation hydrolases, including PuhA, PuhB, LibA, HylA, Phh, Mhh, and LahB, provide new knowledge about the underlying metabolic pathways governing DUR metabolism. The present review summarizes the state-of-the-art knowledge of regarding (1) the environmental occurrence and toxicity of DURdiuron,; (2) newly isolated and identified diuron-degrading microbes and their enzymes/genes; and (3) the bioremediation of DURdiuron in soil and water environments. This review further updates the recent knowledge on bioremediation strategies with a focus on the metabolic pathways and molecular mechanisms involved in the bioremediation of DURdiuron.